2016
DOI: 10.18632/aging.101044
|View full text |Cite
|
Sign up to set email alerts
|

Mutational load of the mitochondrial genome predicts pathological features and biochemical recurrence in prostate cancer

Abstract: Prostate cancer management is complicated by extreme disease heterogeneity, which is further limited by availability of prognostic biomarkers. Recognition of prostate cancer as a genetic disease has prompted a focus on the nuclear genome for biomarker discovery, with little attention given to the mitochondrial genome. While it is evident that mitochondrial DNA (mtDNA) mutations are acquired during prostate tumorigenesis, no study has evaluated the prognostic value of mtDNA variation. Here we used next-generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…To evaluate a correlation of clinical parameters and mtDNA mutation frequency a logistic regression analysis was performed (Supplementary Table 3). Overall mtDNA mutation load correlated significantly with increasing patient age (p = 0.04, likelihood-ratio test), in line with recent reports 9,20,21 and with lower free to total PSA ratios (fPSA%, p = 0.05, likelihood-ratio test, Supplementary Table 3). A low fPSA% value is a prognostic indicator of poor prognosis 22 .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…To evaluate a correlation of clinical parameters and mtDNA mutation frequency a logistic regression analysis was performed (Supplementary Table 3). Overall mtDNA mutation load correlated significantly with increasing patient age (p = 0.04, likelihood-ratio test), in line with recent reports 9,20,21 and with lower free to total PSA ratios (fPSA%, p = 0.05, likelihood-ratio test, Supplementary Table 3). A low fPSA% value is a prognostic indicator of poor prognosis 22 .…”
Section: Resultssupporting
confidence: 88%
“…Sequencing of the mtDNA of our 50 paired samples identified 84 specific HP sites in the tumors and 33 in benign samples, corresponding to a tumor mtDNA HP rate of 1.6 versus 0.6 in the benign tissues. Recent studies of mtDNA NGS reported mutation frequencies ranging from 0.7 to 2.1 per tumor [9][10][11][12]20 (Supplementary Table 6). The landscape study of Hopkins et al, which included samples of 384 PCa patients, reported a rate of 0.8.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we found no correlation between mtDNA content and: (i) tumor size ( P ‐value = 0.47); (ii) distance from the tumor for NAP samples ( P ‐value = 0.63); or (iii) difference between NAP and PCa in the same prostate ( P ‐value = 0.51) (Supplementary Figure S3A‐C); as well as (iv) patients age; or (v) PSA level at diagnosis in PCa ( P ‐values = 0.41 and 0.49, respectively); and NAP samples ( P ‐values = 0.61 and 0.13, respectively). Using published mtDNA variant data available for 112 of the 115 patients included in a previous study, we further found no significant associations between mtDNA content and either the total number of mtDNA variants or number of mtDNA replication D‐Loop region variants ( P ‐values = 0.724 and 0.566, respectively).…”
Section: Resultsmentioning
confidence: 61%
“…-C); as well as (iv) patients age; or (v) PSA level at diagnosis in PCa (P-values = 0.41 and 0.49, respectively); and NAP samples (P-values = 0.61 and 0.13, respectively). Using published mtDNA variant data available for 112of the 115 patients included in a previous study,9 we further found no significant associations between mtDNA content and either the total number of mtDNA variants or number of mtDNA replication D-Loop region variants (P-values = 0.724 and 0.566, respectively).…”
mentioning
confidence: 52%
“…The European comparative cohort included Australian patients selected based on a treatment-naïve surgically removed tumor with a Gleason score !8, as previously described by the Australian Prostate Cancer Centre (APCR; Supplementary Table S1; ref. 15).…”
Section: Patient Description Genetic Ancestries and Ethicsmentioning
confidence: 99%